PENGGUNAAN FlipHTML5 SEBAGAI MEDIA PEMBELAJARAN BAHASA INDONESIA PADA PESERTA DIDIK SDN PANGONGANGAN KOTA MADIUN - Widyaningrum, Widyaningrum; Cahyono, Bambang Eko Hari; Soleh, Dwi Rohman (Wewarah: Jurnal Pendidikan Multidisipliner, 2023)
Penelitian ini mengkaji penggunaan FlipHTML5 untuk pembelajaran bahasa Indonesia di SDN Pangongangan, merinci proses, implementasi, dan tantangan yang dihadapi. Dengan menggunakan metode penelitian deskriptif kualitatif, data dari guru, siswa, peristiwa selama penelitian, dan dokumen seperti silabus dan RPP dianalisis. Temuan menunjukkan bahwa meskipun pembelajaran manual sudah diterapkan, format tulisan siswa kurang menarik. Penerapan FlipHTML5 sudah efektif, namun beberapa siswa menghadapi tantangan seperti kesalahan tautan tugas dan kebingungan terkait pengunduhan file. Masalah internet juga menyebabkan keterlambatan penyerahan tugas.With an emphasis on the procedure, execution, and obstacles faced, this study seeks to explain and detail the usage of FlipHTML5 as a learning medium for Indonesian language training at SDN Pangongangan. Using a qualitative descriptive research methodology, it collects information from SDN Pangongangan instructors and students as well as from events that happened throughout the investigation and documents such lesson plans, syllabi, and research findings and their documentation. The results show that although the learning process has been carried out, it is not supported by interesting forms that would pique students' interest in writing. Students have not yet completely utilized Chromebooks as a learning medium, despite successful manual learning. FlipHTML5 has been implemented well, since most students are able to create FlipBooks with ease. Difficulties encountered include students being confused about how to obtain files from Canva and convert them to FlipHTML5 files, as well as issues in task link submission and the absence of source links in completed work. There were additional delays in certain pupils' task submission due to internet problems